Attosecond light sources in the water window. (17th January 2018) - Ren, Xiaoming; Li, Jie; Yin, Yanchun; Zhao, Kun; Chew, Andrew; Wang, Yang; Hu, Shuyuan; Cheng, Yan; Cunningham, Eric; Wu, Yi; Chini, Michael; Chang, Zenghu
Abstract: As a compact and burgeoning alternative to synchrotron radiation and free-electron lasers, high harmonic generation (HHG) has proven its superiority in static and time-resolved extreme ultraviolet spectroscopy for the past two decades and has recently gained many interests and successes in generating soft x-ray emissions covering the biologically important water window spectral region. Unlike synchrotron and free-electron sources, which suffer from relatively long pulse width or large time jitter, soft x-ray sources from HHG could offer attosecond time resolution and be synchronized with their driving field to investigate time-resolved near edge absorption spectroscopy, which could reveal rich structural and dynamical information of the interrogated samples. In this paper, we review recent progresses on generating and characterizing attosecond light sources in the water window region. We show our development of an energetic, two-cycle, carrier-envelope phase stable laser source at 1.7 μ m and our achievement in producing a 53 as soft x-ray pulse covering the carbon K-edge in the water window. Such source paves the ways for the next generation x-ray spectroscopy with unprecedented temporal resolution.